Desenvolvimento ósseo e estimativa de idade do peixe-boi da Amazônia Trichechus inunguis (Natterer, 1883) por avaliação radiográfica e ultrassonográfica - Brum, Winnie Muniz (Instituto Nacional de Pesquisas da Amazônia - INPA, 2013)
The Amazonian manatee (Trichechus inunguis) is an endemic species of the rivers of the Amazon and listed as vulnerable on Brazil. Studies focusing on aspects of the biology of the species, such as parameters on the chronological age of individuals, are important tools for understanding the life history of these animals. The aim of this study was to describe how ossification occurs in this species and to estimate the age of living individuals using diagnostic imaging methods. Over the years 2011-2012, radiographs and ultrasound exams of the pectoral fins of 72 animals (37 males and 35 females) kept in two research and rehabilitation centers in the state of Amazonas - Brazil, were evaluated for monitoring bone development. It was observed that the species develops slowly without major events, and there is no the sexual dimorphism in the way ossification occurs, although it occurs at different times for each sex. Radiographic methods correctly estimate the age. However, the intervals of estimated ageobtained were too wide. The ultrasound method was flawed. Future longitudinal studies of long duration can be performed to increase the accuracy of the estimates obtained, with smaller chronological windows proposals.
Keywords: Peixe-boi; Sirênios; Trichechus inunguis